Development of a Carbon Paste Electrode Modified with Saffron-Conjugated Silver Nanoparticles for the Simultaneous Determination of Cd, Pb, Zn, Cu and Cl in Soils and Plants - Stella Girousi; Vasiliki Keramari; Ioanna Paraschi; Sophia Karastogianni; Evangelia E. Golia (Chemosensors)
A simple and easily applicable analytical method for the simultaneous determination of Cd2+, Pb2+, Zn2+, Cu2+, and Cl− by applying a modified carbon paste electrode with saffron-conjugated silver nanoparticles (AgNPs@Sa) is being presented. The modified CPE was then used for the simultaneous determination of Cd2+, Pb2+, Zn2+, and Cu2+ as well as chloride ions in soil and plants. The comparative analysis demonstrated a significant enhancement in the applicability of the modified electrode through the incorporation of silver nanoparticles (AgNPs) at the carbon paste electrode (CPE) surface, leading to the development of a poly-Sa-CPE. This newly proposed method offers notably superior qualitative performance compared to other metal nanoparticle-based modifications reported in the literature. The accordingly modified electrode was successfully applied in the development of a chloride ion. A novel sensor is being proposed that makes possible the determination of heavy metals and chlorides in the same solution, in soil and plant samples. The enhanced sensitivity and selectivity of the poly-Sa-CPE system highlights its potential as a more effective alternative for heavy metal and chloride analysis, further demonstrating its advantages in electrochemical applications. The LODs of Cd2+, Pb2+, Zn2+, Cu2+, and Cl− for their simultaneous determination are 0.38 μg·L−1, 0.44 μg·L−1, 0.72 μg·L−1, 0.42 μg·L−1, and 0.11 μg·L−1, respectively, with comparably high relative standard deviations of about 8.1%, 9.4%, 8.3%, 7.6%, and 7.9%, respectively.